THE RELEVANCE OF IDEALISM PHILOSOPHY TO THE TRANSFORMATION OF FREEDOM CURRICULUM - Prayetno, Eko; Ma'ali, Abul; Al-Ghatnaini, Raed Awadh Saeed; Saelaemae, Tasnim (INTIHA: Islamic Education Journal, 2025)
Educators must take control of the philosophical foundations of education for two key reasons. First, education is inherently normative; it requires prescriptive guiding principles, not merely descriptive. A philosophical understanding provides a framework to determine what should be done in education rather than observing it passively. Without such a foundation, education risks being misunderstood or reduced to mere technical practices, ignoring its deeper humanistic and moral dimensions. Second, while valuable, a purely scientific approach to education is insufficient. Education must be viewed holistically, and philosophy offers that comprehensive lens. Different philosophical schools, including Idealism, Realism, and pragmatism, present varied educational aims and methods interpretations. Among these, Idealism, which this paper focuses on, emphasizes the development of the mind and personality as the core purpose of education. In the Indonesian context, Pancasila serves as the foundational philosophy, shaping the nation's educational values. While exploring global philosophical perspectives is important, educational systems must align with Pancasila to remain culturally and ideologically grounded. Philosophical literacy allows educators to engage with ideas critically, filter those incompatible with national values, and incorporate those that enrich understanding without conflict. By revisiting and strengthening the philosophical foundations of education, especially through the lens of Idealism, educators can better understand their practice's purpose, direction, and ethical dimensions. This, in turn, supports the creation of meaningful, value-based educational experiences beyond procedural knowledge.